The effects of prenatal and early-postnatal ethanol exposure on rat brain neurochemistry and behaviour - Swart, Patricia Cathryn (Department of Human Biology, 2023)
Foetal alcohol spectrum disorder (FASD), the umbrella term used to describe the wide range of cognitive and behavioural deficits observed after exposure to alcohol in utero, is a major public health issue specifically in South Africa. South Africa is thought to have the highest prevalence of FASD in the world. FASD presents as a variety of learning and memory deficits as well as psychological disorders such as anxiety and depression but the underlying mechanisms are largely unknown and poorly understood. FASD, learning and memory processes and psychological disorders have been associated with changes in neural plasticity. Therefore, the research reported in this thesis describes ethanol-induced changes in neuroplasticity-related proteins, with specific reference to the extracellular signal-regulated kinase1/2 (ERK1/2) and glycogen synthase kinase-3-beta (GSK3β) signalling cascades, using two different animal models of FASD. Further, to elucidate additional mechanisms underlying the deficits observed in FASD, proteomic profiles were determined in order to illustrate largescale ethanol-induced changes in proteins involved in energy metabolism, neurotransmitter signalling, redox regulation, protein metabolism and cytoskeletal structure in the rat brain. In addition, this research describes vinpocetine, a phosphodiesterase (PDE) type 1 inhibitor, as a possible treatment for disturbances caused by early exposure to ethanol and investigates the effects of additional early-life stress in animal models of FASD. The first study, using a third-trimester equivalent animal model of FASD (4 g/kg/day i.p., 12 % v/v, P4 - P9), investigated early-postnatal ethanol-induced changes in adolescent rats. The results demonstrate that significant ethanol-induced changes can occur in rats that do not display overt behavioural deficits. Specifically, early-postnatal ethanol exposure decreased ERK1/2 activation in the prefrontal cortex (PFC) and increased ERK1/2 activation in the dorsal hippocampus (DH). Proteomic analysis revealed additional region-specific changes, for example, early-postnatal ethanol exposure increased the capacity for energy production in the PFC whereas in the DH, energy-related proteins were decreased compared to non-exposed controls. The PFC of rats exposed to early-postnatal ethanol was further characterized by an increased capacity for oxidative phosphorylation coupled with decreased antioxidant capacity. In addition, there was evidence that could lead to altered redox protein signaling in the DH of ethanol rats. Vinpocetine treatment of rats exposed to ethanol during early developmentreduced ethanol-induced changes in ERK1/2 activity in the PFC and DH. Additional proteomic analysis of the ventral hippocampus (VH) demonstrated that vinpocetine also reduced postnatal-ethanol-induced changes in proteins related to energy metabolism, signaling, protein synthesis and cytoskeletal structure. Therefore, vinpocetine treatment of rats exposed to earlypostnatal ethanol in conjunction with proteomic analysis has the potential to identify novel treatment targets to reduce the effects of ethanol on the developing brain. The second animal study combined prenatal-ethanol exposure (0.066 % saccharin-sweetened, 10 % ethanol) with the maternal separation model of early-life stress (3 hours/day P2 – P14) in order to account for possible effects of early-life adversity in addition to in utero alcohol exposure. Adult rats exposed to prenatal-ethanol showed reduced weight gain, hyperactivity and a negative affective state which are characteristic of FASD. However, the combination of prenatal-ethanol exposure and early-life stress did not enhance behavioural changes. Rather, early-life stress subsequent to prenatal-ethanol exposure proved beneficial as shown by similar weight gain and activity levels to that of control rats. Similarly, early-life stress reduced prenatal-ethanol-induced increase in P-ERK1/2 signalling in both the PFC and DH. On the contrary, the combination of prenatal-ethanol exposure and early-life stress seemed to have an additive effect on protein changes in the PFC of adult rats as shown by a greater number of proteins related to energy, redox regulation, signaling and cytoskeletal structure being altered by the combination of these developmental insults. In addition, the DH appeared to be more susceptible to prenatal-ethanol exposure since a greater number of proteins were significantly changed by prenatal-ethanol exposure. However, the combination of prenatal-ethanol and maternal separation stress reduced the number of significantly altered proteins in the DH. These results further highlight the wide range and region-specific effects of prenatal-ethanol exposure on the brain and importantly demonstrate an interaction between prenatal-ethanol exposure and early-life stress. Therefore, it is important to account for the possible effects of early-life adversity when modeling FASD. Results from these 2 studies highlight the long-term effects of ethanol exposure during early development on the rat brain and behaviour. In addition, these studies describe the importance of age at behavioural testing and tissue analysis and demonstrate the complexity of modeling FASD. Importantly, results demonstrate the need to account for the possible effects of earlylife adversity when modeling FASD. Further, the results presented in this thesis highlight thebenefits of performing neurochemical analyses on rats that have not been subjected to prior stressors other than the model being investigated and further, to separately analyze functionally distinct brain regions. Both studies demonstrate long-term ethanol-induced changes in PERK1/ 2 signalling and proteins related to energy metabolism and redox regulation in the PFC and DH. These results provide a platform for future research with the potential to identify novel treatment targets. Together, the results presented in this thesis contribute valuable insight to the field of FASD and the animal models used to study this multifaceted disorder.